CPT-Based Control Strategy for a Two-Phase Three-Wire Pv Inverter: a Multifunctional Perspective and a Comprehensive Review - Augusto M. S. Alonso; João H. Oliveira; Danilo I. Brandao; Jakson P. Bonaldo; Helmo K. M. Paredes; Fernando P. Marafao (Eletrônica de Potência, 2022)
Multifunctional inverters play an important role in electrical grids due to their capability to provide active power conversion from photovoltaic (PV) systems, as well as by concomitantly offering ancillary services that provide grid support and power quality improvement. Although control strategies for such inverters have been extensively explored for applications in single- and three-phase grids, their consideration for the two-phase three-wire topology has been superficially discussed in literature. Thus, first, this paper contributes to the literature by presenting a comprehensive review about the control of power electronic inverters in two-phase three-wire grids. As second contribution, this paper proposed a flexible control strategy based on the Conservative Power Theory capable of adequately synthesizing control references for a PV-based multifunctional inverter operating in a two-phase three-wire grid. Additionally, power quality services can be selectively offered by the inverter to achieve compensation of reactive, harmonic and unbalance current terms, as well as providing reduction in neutral currents. Hardware-in-the-loop experimental results comprising a multifunctional PV inverter under several scenarios of operation are shown to demonstrate and validate the flexibility of the method.